The Impact Of Environmental Turbulence On Organizational Learning - Kipley, Dan; Helm-Stevens, Roxanne; Lookinbee-Kipley, Mitchell (Archives of Business Research, 2018)
Organizational learning (OL) is an area of business study that is continually expanding and developing new methods for effectively responding to the dynamic and disruptive shifts that occur in the environment. Firms that are best able to envisage and interpret environmental shifts and then proactively position their organization through an effective system of OL will increase the probability of developing a source of competitive advantage. This advantage centers on the organizations ability to interpret the external data and apply this knowledge to the capabilities processes used by the organization. Through application of this knowledge, research has shown that enhanced organizational capabilities performance such as increasing the speed of fostering innovation, product/market creativity, knowledge application and transfer will occur, to name but a few, will occur. As a firm’s organizational learning process is influenced by and in many cases rooted in their responsiveness to the environmental turbulence, a reasonable extension of logic would be that the environment turbulence has an effect on the efficacy of organizational learning. Properly designed and implemented organizational learning processes are key for organizations to assess the true level of environmental turbulence. Only by evaluating and responding to a properly assessed level of turbulence can the firm align their capabilities with their strategy. Therefore, in order to outperform the competitors, organizations will need to be more proactive in creating its “future by design” which requires more creative strategic “thinking” rather than “planning” in the rigid, traditional manner.